Does vaccination in solid organ transplant recipients result in adverse immunological sequelae? a systematic review and meta-analysis - Mulley, W; Dendle, C; Ling, JX; Knight, SR (Elsevier, 2018)
Background: Clinical guidelines recommend vaccinations for solid-organ transplant recipients. However, concern exists that vaccination may stimulate adverse alloimmune responses. Methods: We systematically reviewed the published literature regarding this aspect of vaccine safety. Electronic databases were searched for interventional and observational studies assessing de novo donor-specific antibodies (DSA) and rejection episodes after vaccination against infectious pathogens. Graft loss was also assessed. A meta-analysis was conducted for prospective, controlled studies. PRISMA reporting guidelines were followed. Results: Ninety studies (15,645 vaccinated patients and 42,924 control patients) were included. Twelve studies included control groups. The incidence of de novo DSA (14 studies) was 23 of 1,244 patients (1.85%) at 21 to 94 days. The incidence of rejection (83 studies) was 107 episodes in 5,116 patients (2.1%) at 0.7 to 6 months. Meta-analysis of prospective controlled studies (n = 8) showed no increased rejection risk with vaccination compared with no vaccination (RR 1.12, 95% CI 0.75 to 1.70). This finding was supported by data from 3 registry analyses. Conclusions: Although the current evidence lacks high-quality, controlled studies, the currently available data provide reassurance that clinicians should recommend appropriate vaccination for their transplant patients as the risk of de novo DSA and rejection is relatively low.